Influence of Ketogenic Diet and Nutraceutical Correction in the Complex Treatment of Lower Limbs Lipedema - Tatyana V. Apkhanova; Valery N. Sergeev; Marina M. Krukova; Valeria A. Vasilyeva; Detelina B. Kulchitskaya; Tatyana V. Konchugova; Sergey V. Sapelkin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Currently, the ketogenic diet (KD) is used to treat obesity. A prospective study on the use of KD and nutraceutical correction of the nutritional status of patients with lipedema was carried out.